Tackling Negative Symptoms of Schizophrenia with Memantine - Antonios Paraschakis (Case Reports in Psychiatry)
We present a case of a 52-year-old male patient suffering from chronic schizophrenia stabilized on risperidone long-acting injection (37,5 mg/2 weeks) and biperiden 4 mg/day. Residual symptoms are affective flattening, alogia, avolition, and asociality. Memantine 10 mg/day was added. After 1.5 months, the patient spontaneously referred to “feel better being in company of my relatives.” The following scales have been completed: the Scale for the Assessment of Negative Symptoms (96), the Scale for the Assessment of Positive Symptoms (3), the Mini Mental Scale Examination (26), and the Calgary Depression for Schizophrenia Scale (2). Memantine was increased to 20 mg/day and biperiden was decreased to 2 mg/day. Two months later, apathy and asociality considerably improved and affective flattening, alogia, and attention slightly got better (SANS 76, SAPS 1, MMSE 26, and CDSS 1). After two more months, the improvement continued in the same domains (SANS: 70, SAPS: 1 MMSE: 27, and CDSS: 1). Positive symptoms remained in full remission. It has been hypothesized that one of the causes of schizophrenia is glutamate excitotoxicity. Memantine, a glutamate receptor antagonist, could possibly ameliorate schizophrenia symptoms, the negative ones among them, used as add-on therapy to atypical antipsychotics. Memantine could be of potential help in schizophrenia patients with severe residual negative symptoms.